Upaya Peningkatan Kesadaran Siswa dalam Pelaksanaan Sholat Dzuhur Berjamaah (Studi Kasus di MAN 1 Ternate) - M. Bahtiar Tahir; Neisha Putri Muhammad; Delany Oktashela Dedy; Afdal Abdullah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Efforts to Increase Student Awareness in the Implementation of Dzuhur Prayer in Congregation (Case Study at MAN 1 Ternate). This study aims to determine the Efforts to increase student awareness in carrying out Dzuhur prayer in congregation at Man 1 Ternate. The type of research used is descriptive research. Through a qualitative approach, the study involved interview and documentation data collection methods. The results of the study showed that there were still many students who had reasons for not performing prayers. The implementation of Dzuhur prayer in congregation tends to be carried out for male students, but for female students, most of them did not perform Dzuhur prayer due to excuses, cleanliness of the prayer room, and teachers who use prayer time to continue learning. Efforts to increase awareness in Dzuhur prayer in congregation include cleaning the prayer room twice a week, providing an understanding of the importance of congregational prayer, making absence excuses for female students, and providing understanding and asking for cooperation from all teachers so that they can comply with the time for implementing Dzuhur prayer in congregation at the madrasah.